PENDAMPINGAN PENGOLAHAN LIMBAH INDUSTRI IKAN MENJADI NATURAL SEASONING PRODUCT: TRANSFER TEKNOLOGI ANTIMIKROBA DI PEKON WALUR, PESISIR BARAT - Dewi Sartika; Hengki Mayaguezz; Gigih Forda Nama; Dikpride Despa; Mardiana Mardiana; Sela Julita; Puan Mutia Ayunisa (Universitas Mataram, 2026)
Fishery waste is generally not utilized and is often discarded, causing accumulation, decay, and environmental pollution. Pesisir Barat Regency is famous for its fishery potential and is the largest producer of Tuhuk (Blue Marlin) fish. Arista UMKM is one of the UMKM producing fish floss and its derivatives. The lack of knowledge among UMKM centers regarding the processing of fish waste into value-added products has led to the accumulation of fishery waste. The technologies to be disseminated are: a) Antimicrobial Technology, b) Simple Food Processing Technology, c) Waste Processing Technology into Natural Seasoning Products. The purpose of this community service is 1) to transfer simple food processing technology; 2) to solve partner waste problems by minimizing waste into marketable products; 3) to increase partner income with a new product, namely Natural Seasoning Products. The methods used are: a) lectures and discussions on simple food processing technology, b) technology transfer for the production of Natural Seasoning Products, c) assistance in the processing of Natural Seasoning Products. The evaluation of the community service program is conducted by measuring understanding at the beginning (pre-test) and at the end of the community service activity (post-test). The results of this community service activity show that there is a lack of knowledge among partners and the surrounding community regarding fish waste that can be processed into useful products, knowledge related to microbes, antimicrobials, processing waste into cooking spices, and knowledge of efforts to protect the environment by processing waste into products. After providing explanations, presenting materials, holding question and answer discussions, and conducting hands-on practice, there was an increase in the understanding of Arista UMKM partners and the surrounding community regarding simple food processing and antimicrobial technology, ranging from 57-100% (post-test results). The increase in the partners' skill scores in Natural Seasoning Product processing technology was significant, reaching 100% (post-test results). The conclusion is that the technology transfer used, namely the processing of fish waste into natural seasoning products, has commercial value, therefore minimizing waste in the environment and making it beneficial. This product can be commercialized, which is expected to increase the income of Arista UMKM partners.